NAMING OF GENERATIONS AS AN INDICATOR OF AXIOLOGICAL PRIORITIES IN LANGUACULTURES OF BELARUS, RUSSIA, AND THE NETHERLANDS - Садовская, Екатерина (SWorldJournal, 2020)
the abstract deals with the problematics of axiological priorities through the analysis of the naming of generations in such countries as Belarus, Russia, and the Netherlands that demonstrate differences in comparison with the widely accepted American gen